None.
Whatever number you substitute for 'x', 0x will always be 0,
and the equation will always become [ 0 = 4 ].
No value of 'x' can make [ 0 = 4 ]. There is no solution.
x2 - 21x = 72x2 - 21x - 72 = 0(x - 24) (x + 3) = 0x = 24x = -3
x2-14x+45=0(x-9)(x-5)=0x-9=0 & x-5=0x=9 & x=5
This is always true! According to the Additive Inverse Axiom -X+X always equals 0 which is equivalent to 0X.
x2 = 8xx2- 8x = 0x(x - 8) = 0x = 0 ;x - 8 = 0x = 8
x+(-2.5)+6.8=0x+(-2.5+6.8)=0x+(4.3)=0x+4.3=0Subtract 4.3 from both sides and you get:x= -4.3
-28
An equation must have 1, 0, or infinitely many solutions. So if you find 1 and there is another, you have know it has infinitely many. For example. 0x+2=2 I solve this and the equations become 0x=0 Now, 1 is a solutions, but so is 2. I now know there are infinitely many. How about 0x+2=3. No solution and 2x+2=4, has one solution. I put those two here so you might try other numbers and see that they have no solutions and one solution. A special type of equation known as an identity is an equation that holds for all numbers. This means it has infinitely many solutions.
x2 - 21x = 72x2 - 21x - 72 = 0(x - 24) (x + 3) = 0x = 24x = -3
There is no value of x that satisfies the equation. You may be missing an operator (+. - sign).
x3+13x2=-22xadd 22x to both sides:x3+13x2+22x=0now factor:x(x2+13x+22)=0x(x+11)(x+2)=0x=0x+11=0x+2=0Therefore the solution to this equation is x=0, x=-11, x=-2
x+1=x+2 x=1+2+x 0x=1+2 0x=3 0x=/=3 (=/= means does not equal) so there is no solution
have to put it was 2x and not x2--back to the problem--2x-x-4=0x=4* * * * *True, but the question, in all likelihood WAS x2 - x - 4 = 0and the solutions to that equation are -1.561553 and 2.561553
x2-14x+45=0(x-9)(x-5)=0x-9=0 & x-5=0x=9 & x=5
x-2/3 = 0x - 5/7 = 0(x-2/3)(x-5/7) = 0x^2 -2/3(x) -5/7(x) + 10/21 = 0x^2 -14/21(x) - 15/21(x) +10/21 = 0x^2 -29/21(x) +10/21 = 0Another Answer:-If: x = 2/3 and x = 5/7Then: (3x-2)(7x-5) = 0Multiplying out the brackets: 21x2-29x+10 = 0 which is the equation.Check using the quadratic equation formula: x = 2/3 and x = 5/7
x2 - 21x = 72x2 - 21x - 72 = 0(x - 24) (x + 3) = 0x = 24x = -3
x2 - 5x = 0x (x - 5) = 0x = 0andx = 5
This is always true! According to the Additive Inverse Axiom -X+X always equals 0 which is equivalent to 0X.